ANALISIS KEMAMPUAN MENULIS TEGAK BERSAMBUNG KELAS V SDN KARANGANYAR GUNUNG 02 - Arif Dias Artama; Farida Nursyahidah; Noor Miyono (STKIP Subang, 2023)
This research is motivated by the difficulties and long time taken by students in class V C when given writing tasks using cursive handwriting. Some students also struggle with writing proper shapes and curves in cursive writing. Consequently, these frequently encountered issues lead many students to not apply cursive writing in their daily writing activities. Moreover, cursive writing activities are necessary to stimulate brain function, particularly the right brain hemisphere responsible for various forms of art and aesthetics, and the left brain hemisphere as the generator of words, ideas, and concepts to be written. The main problem under investigation is the cursive writing ability of class V C students at Karanganyar Gunung 02 Elementary School.